Research and development—where people are exposed to nanomaterials. Issue 2 (25th April 2015) - Imhof, Chantal; Clark, Katherine; Meyer, Thierry; Schmid, Kaspar; Riediker, Michael
Abstract : Research and development—where people are exposed to nanomaterials: Chantal IMHOF, et al . Institute for Work and Health, Universities of Lausanne and Geneva, Switzerland Objective: Many nanomaterials (materials with structures smaller than 100 nm) have chemical, physical and bioactive characteristics of interest for novel applications. Considerable research efforts have been launched in this field. This study aimed to study exposure scenarios commonly encountered in research settings. Methods: We studied one of the leading Swiss universities and first identified all research units dealing with nanomaterials. After a preliminary evaluation of quantities and process types used, a detailed analysis was conducted in units where more than a few micrograms were used per week. Results: In the investigated laboratories, background levels were usually low and in the range of a few thousand particles per cubic centimeter. Powder applications resulted in concentrations of 10, 000 to 100, 000 particles/cm 3 when measured inside fume hoods, but there were no or mostly minimal increases in the breathing zone of researchers. Mostly low exposures were observed for activities involving liquid applications. However, centrifugation and lyophilization of nanoparticle‐containing solutions resulted in high particle number levels (up to 300, 000 particles/cm 3 ) in work spaces where researchers did not always wear respiratory protection. No significant increases were found for processes involving nanoparticles bound to surfaces, nor were they found in laboratories that were visualizing properties and structure of small amounts of nanomaterials. Conclusions: Research activities in modern laboratories equipped with control techniques were associated with minimal releases of nanomaterials into the working space. However, the focus should not only be on processes involving nanopowders but should also be on processes involving nanoparticle‐containing liquids, especially if the work involves physical agitation, aerosolization or drying of the liquids.